Improvement of safety of surgical interventions in patients with ventral and postoperative ventral hernia under conditions of different types of hernioplasty - V. I. Piatnochka (Kazimierz Wielki University, 2018)
The progress of surgery is impossible without continuous analysis of medical errors and complications, without identifying and eliminating their causes for the development and implementation of measures to improve the safety of surgical interventions. Objective: to develop technical preconditions for improving the safety of surgical interventions in this category of patients according to the results of surgical treatment of patients with primary and incisional ventral hernias. Materials and methods. Between 2001 and 2017, 1419 patients with primary ventral hernia and incisional hernia underwent surgical intervention. The distribution of patients into groups occurred according to the periods of surgical treatment of patients: from 2001 to 2009 and from 2010 to 2017. In the first period, 597 (42.07 %) patients were examined and operated. These patients formed a comparison group. The main group in the period from 2010 to 2017 made 822 (57.93 %) persons. The results of investigation. In the period from 2010 to 2017, the technique of preventive hernioplasty was used in 124 (15.08 %) patients. The decrease in the number of such operations in 2.53 times compared with the comparison group is explained by the wider introduction to the surgical practice of alloplastic methods of surgical intervention. However, this operation remains the method of choice in the following cases: when small hernial defects in young people, in the absence of morbid obesity and syndrome of undifferentiated connective tissue dysplasia (UCTD); in patients of senile and elderly age with a high comorbidity index and higher classes of anesthetic-operational risk (class according to ASA III-IV); and in the absence of the technical skills of the alloplastic methods of hernioplasty of the operating surgeon. In the main group of operating patients, the dominance of using the "sublay" method was noted - 354 (52.21 %) versus 209 (30.83%) of the "on lay" method and 90 (13.27 %) of the "inlay" method. In addition, in this group 45 (5.47 %) patients underwent the method of anatomical separation of the anatomical components of the anterior abdominal wall (CST). Among them, 20 (44.44 %) - in the original performance and 25 (55.56%) - in combination with the use of PPM. Conclusions. An individualized approach to each individual patient significantly reduced the number of both early and local as well as late postoperative complications. The technical improvement of the existing methods of hernioplasty and the development of new ones greatly reduced the number of postoperative complications and increased the safety of surgical interventions in patients with ventral and incisional ventral hernia.